2020
DOI: 10.1002/ptr.6690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fenugreek consumption on serum lipid profile: A systematic review and meta‐analysis

Abstract: Various studies have shown that Trigonella foenum‐graecum (fenugreek) supplementation has lipid‐lowering activity. This meta‐analysis was performed to evaluate the effect of fenugreek supplementation on human serum lipid profile. Data sources were PubMed, EMBASE, Scopus, and Coherence library which were searched systematically from January 2000 up to December 2019. Inclusion criteria were randomized clinical trial (RCT) study design, at least one of lipid profile components (triglyceride [TG], total cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 41 publications
0
26
1
Order By: Relevance
“…Thirteen of these studies were excluded because they included an abstract ( N = 5) or a protocol ( N = 1) only, were not published in English ( N = 1), had inappropriate exposures ( N = 2) or outcomes ( N = 1), or did not provide updated data ( N = 2). As a result, 50 systematic reviews and meta‐analyses were included in the final analysis (Figure 1; Amir Shaghaghi et al, 2013; Askari et al, 2019; Azhdari et al, 2019; Chen et al, 2020; Fatahi et al, 2019; Ghaedi et al, 2019; Ghaedi et al, 2020; Glisic et al, 2018; Gui et al, 2016; Hadi et al, 2018, 2020; Hadi, Pourmasoumi, Mohammadi, et al, 2019; Hadi, Pourmasoumi, Najafgholizadeh, et al, 2019; Hallajzadeh et al, 2020; Hamedifard et al, 2019; Han et al, 2019; Hasani et al, 2019; Hemati et al, 2020; Hernández‐García et al, 2019; Heshmat‐Ghahdarijani et al, 2020; Karimian et al, 2019; Khorshidi et al, 2020; Li et al, 2014, 2015, 2020; Maierean et al, 2017; Mansour‐Ghanaei et al, 2018; Mohammadi, Hadi, et al, 2019; Mohammadi, Ramezani‐Jolfaie, et al, 2019; Ostadmohammadi et al, 2019; Pourmasoumi et al, 2018, 2020; Rahmani et al, 2019; Rahmani et al, 2020; Ricci et al, 2010; Ried, 2016; Rocha et al, 2019; Sahebkar, 2014; Sahebkar, Simental‐Mendía, et al, 2016; Sahebkar, Soranna, et al, 2016; Salehi‐Sahlabadi et al, 2020; Serban et al, 2015; Shekarchizadeh‐Esfahani et al, 2020; Taku et al, 2010; Ursoniu et al, 2018; Zhang et al, 2020; Zhang, Yuan, et al, 2016; Zhang, Liu, et al, 2016; Zhu et al, 2017; Ziaei et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen of these studies were excluded because they included an abstract ( N = 5) or a protocol ( N = 1) only, were not published in English ( N = 1), had inappropriate exposures ( N = 2) or outcomes ( N = 1), or did not provide updated data ( N = 2). As a result, 50 systematic reviews and meta‐analyses were included in the final analysis (Figure 1; Amir Shaghaghi et al, 2013; Askari et al, 2019; Azhdari et al, 2019; Chen et al, 2020; Fatahi et al, 2019; Ghaedi et al, 2019; Ghaedi et al, 2020; Glisic et al, 2018; Gui et al, 2016; Hadi et al, 2018, 2020; Hadi, Pourmasoumi, Mohammadi, et al, 2019; Hadi, Pourmasoumi, Najafgholizadeh, et al, 2019; Hallajzadeh et al, 2020; Hamedifard et al, 2019; Han et al, 2019; Hasani et al, 2019; Hemati et al, 2020; Hernández‐García et al, 2019; Heshmat‐Ghahdarijani et al, 2020; Karimian et al, 2019; Khorshidi et al, 2020; Li et al, 2014, 2015, 2020; Maierean et al, 2017; Mansour‐Ghanaei et al, 2018; Mohammadi, Hadi, et al, 2019; Mohammadi, Ramezani‐Jolfaie, et al, 2019; Ostadmohammadi et al, 2019; Pourmasoumi et al, 2018, 2020; Rahmani et al, 2019; Rahmani et al, 2020; Ricci et al, 2010; Ried, 2016; Rocha et al, 2019; Sahebkar, 2014; Sahebkar, Simental‐Mendía, et al, 2016; Sahebkar, Soranna, et al, 2016; Salehi‐Sahlabadi et al, 2020; Serban et al, 2015; Shekarchizadeh‐Esfahani et al, 2020; Taku et al, 2010; Ursoniu et al, 2018; Zhang et al, 2020; Zhang, Yuan, et al, 2016; Zhang, Liu, et al, 2016; Zhu et al, 2017; Ziaei et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐five of these studies were published in the last 3 years. Reanalysis was conducted for a systematic review without meta‐analysis ( N = 1; Rocha et al, 2019), studies that did not report I 2 values ( N = 4; Maierean et al, 2017; Mohammadi, Ramezani‐Jolfaie, et al, 2019; Sahebkar, Simental‐Mendía, et al, 2016; Ursoniu et al, 2018), and studies that reported SMDs ( N = 2; Gui et al, 2016; Heshmat‐Ghahdarijani et al, 2020; Figures S1–S34). The effects of 35 PNSs on the levels of different biomarkers related to hypertension [systolic blood pressure (SBP, mmHg) and diastolic blood pressure (DBP, mmHg)], dyslipidemia [total cholesterol (TC, mg/dl), triglycerides (TG, mg/dl), high‐density lipoprotein cholesterol (HDL‐C, mg/dl), low‐density lipoprotein cholesterol (LDL‐C, mg/dl), the LDL‐C/HDL‐C ratio, very low‐density lipoprotein cholesterol (VLDL‐C, mg/dl), apolipoprotein (Apo)‐AI (g/L), Apo‐B (g/L), Apo‐B/Apo‐AI ratio, plasma lipoprotein (mg/dl), and free fatty acid (mg/dl)], and diabetes [fasting or postprandial glucose (mg/dl), insulin level (mg/dl), glycated hemoglobin (HbA1c, %), and homeostatic model assessment of insulin resistance (HOMA‐IR)] were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e mentioned compound contains Trigonella foenum-graecum (fenugreek, in Persian: "Shanbalileh"), Portulaca oleracea (purslane, in Persian: "Khorfeh"), and Rhus corindria (sumac, in Persian: "Somagh"), all of which have individually various medical effects on lipid profile [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…
Cardiovascular diseases are currently the leading cause of death globally, accounting for about one-third of all deaths (Hadjiphilippou & Ray, 2019;Yusuf et al, 2020). Dyslipidemia is a major risk factor for the development and progression of cardiovascular diseases (Kopin & Lowenstein, 2017;Pan et al, 2016).Dyslipidemia is an incurable but controllable condition characterized by elevated plasma triglycerides (TG), total cholesterol (TC), or low-density lipoprotein cholesterol (LDL) concentrations and decreased plasma high-density lipoprotein cholesterol (HDL) concentrations (Hedayatnia et al, 2020;Heshmat-Ghahdarijani et al, 2020). Previous studies have shown that controlling blood lipids can effectively reduce the risk of cardiovascular diseases (Ida
…”
mentioning
confidence: 99%